2015
DOI: 10.1108/ijdrbe-08-2014-0062
|View full text |Cite
|
Sign up to set email alerts
|

Improving the social performance of flash flood early warnings using mobile services

Abstract: Purpose – The purpose of this study is to provide recommendations for improving the social performance of warnings using mobile services in flash flood prone communities. A warning cannot be considered effective until it is received, understood and responded to by those at risk. This is defined as the social performance of warning communication techniques. Mobile services offer opportunities for improving this, particularly in Bangladesh, but have been underutilised. In this research, character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 9 publications
(5 reference statements)
0
20
0
Order By: Relevance
“…An early warning system can only be effective if the warnings produced are received, understood, trusted, and responded to by the end users (Molinari and Handmer 2011;Cumiskey et al 2015;Zia and Wagner 2015). Young people have an important contribution to make in creating and implementing such ''people-centered'' early warning systems (Basher 2006).…”
Section: Tool 3: Enhancing Preparednessmentioning
confidence: 99%
“…An early warning system can only be effective if the warnings produced are received, understood, trusted, and responded to by the end users (Molinari and Handmer 2011;Cumiskey et al 2015;Zia and Wagner 2015). Young people have an important contribution to make in creating and implementing such ''people-centered'' early warning systems (Basher 2006).…”
Section: Tool 3: Enhancing Preparednessmentioning
confidence: 99%
“…CC BY 4.0 License. dissemination was widely accepted (Cumiskey et al, 2015). However, respondents indicated that remote areas could experience shortage of electricity for long periods, making those devices less reliable.…”
Section: Impact-based Warning Message (Step 3)mentioning
confidence: 99%
“…Cumiskey et al, 2015;Koks et al, 2015;Fakhruddin et al, 2015;Rahman et al, 2012. Response capability Information on impacts and advisories Messages must contain information on the expected impacts and the advisories on how to implement risk mitigation actions. Shah, 2012;Basher, 2006.…”
Section: Multiple Dissemination Channelsmentioning
confidence: 99%
See 2 more Smart Citations